Back side ablation of SiC diodes using a q-switched NIR laser - Adelmann, Benedikt; Hürner, Andreas; Roth, Gian-Luca; Hellmann, Ralf (Journal of Laser Micro Nanoengineering, 2015)
We study pulsed fiber laser back side ablation of silicon carbide diodes. With the objective to thin the SiC substrate thickness without damaging the semiconductor device or altering its electrical characteristics, we investigate the ablation characteristics of silicon carbide and determine the ablation threshold, rate and quality as well as the material composition at the ablated surface. Based on optimized process parameters, including track distance, laser repetition rate and scanning velocity, we micro structure the substrate of SiC diodes and compare its electrical characteristic to an unprocessed device. Our results prove that the typical diode characteristic and built-in voltage are not affected by the laser ablation process. Fiber laser back side ablation therefore offers a precise and efficient micro structuring approach for substrate thinning in silicon carbide technolog
Keywords: Laser ablation; Fiber laser; SiC diode; Serial resistance